2021
DOI: 10.37934/arfmts.87.3.3139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesh Type on Numerical Computation of Aerodynamic Coefficients of NACA 0012 Airfoil

Abstract: Mesh type and quality play a significant role in the accuracy and stability of the numerical computation. A computational method for two-dimensional subsonic flow over NACA 0012 airfoil at angles of attack from 0o to 10o and operating Reynolds number of 6×106 is presented with structured and unstructured meshes. Steady-state governing equations of continuity and momentum conservation are solved and combined with k-v shear stress transport (SST-omega) turbulence model to obtain the flow. The effect of structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Budiyanto et al, [14] analyzed the performance of thermoelectric coolers to decrease the temperature of electric motors and concluded that it can reduce the temperature of the motor significantly. Abobaker et al, [15] performed a mesh quality study over an airfoil using structured and unstructured mesh and concluded that structured mesh results are closer to the experimental data for the calculation of drag and lift forces. Mohamed et al, [16] studied the heat transfer rate of automotive radiator using an active louvered fin with shape memory alloy by varying the fin pitch, louver angle and wall temperature.…”
Section: Introductionmentioning
confidence: 92%
“…Budiyanto et al, [14] analyzed the performance of thermoelectric coolers to decrease the temperature of electric motors and concluded that it can reduce the temperature of the motor significantly. Abobaker et al, [15] performed a mesh quality study over an airfoil using structured and unstructured mesh and concluded that structured mesh results are closer to the experimental data for the calculation of drag and lift forces. Mohamed et al, [16] studied the heat transfer rate of automotive radiator using an active louvered fin with shape memory alloy by varying the fin pitch, louver angle and wall temperature.…”
Section: Introductionmentioning
confidence: 92%
“…The container ship Fortune Freighter is selected to be the reference vessel. The principal parameters and geometry of this ship are depicted in Table 1 and Figure 1 [18].…”
Section: Numerical Setup 31 Reference Vesselmentioning
confidence: 99%
“…The type and quality of the mesh plays a very important role in order to get high accuracy of numerical calculations and mesh quality is also very important to match and validate with the geometry [21]. Furthermore, the proper turbulence model should be determined after selecting the type and quality of the mesh.…”
Section: Meshing and Cfd Governing Equationmentioning
confidence: 99%